EMPATHY POLITICS VERSUS TERRORISM: THE NEW ZEALAND PRIME MINISTER JACINDA ARDERN’S POLITICAL LEADERSHIP COMMUNICATION - Andika Hendra Mustaqim (IAIN Salatiga, 2019)
This research explores the political communication by New Zealand Prime Minister JacindaArdern in the face of terror attacks of two mosques in Christchurch on March 15, 2019. The emphasis of research is empathy politics in a narrow framework and broader framework, namely the humanitarian framework. The study used the method of analyzing the content of speeches and Ardern statements and case studies with qualitative approaches and critical constructivist paradigms. The results of the study are Prime Minister JacindaArdern using various models and ways to show political communication in handling terror attacks against two mosques in Christchurch. The politics of tears is played as a form of empathy politics. Protection from minorities was also shown by Ardern. Hug is a form of political action to embrace. Ardern often gives greetings typical of Muslims.